2020
DOI: 10.1073/pnas.1920086117
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid hormone receptors mediate two distinct mechanisms of long-wavelength vision

Abstract: Thyroid hormone (TH) signaling plays an important role in the regulation of long-wavelength vision in vertebrates. In the retina,thyroid hormone receptor β(thrb) is required for expression of long-wavelength-sensitive opsin (lws) in red cone photoreceptors, while in retinal pigment epithelium (RPE), TH regulates expression of a cytochrome P450 enzyme,cyp27c1, that converts vitamin A1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 46 publications
(62 reference statements)
4
57
0
1
Order By: Relevance
“…1H) manifested a massive reduction of both lws1 and lws2 expression and a concomitant increase in sws1 expression in the larval eyes ( Fig. 1I) as reported in previous studies (16,(26)(27)(28). We noticed that thrb ja27 mutant exhibited a moderate but significant increase in sws2 gene expression ( Fig.…”
supporting
confidence: 86%
“…1H) manifested a massive reduction of both lws1 and lws2 expression and a concomitant increase in sws1 expression in the larval eyes ( Fig. 1I) as reported in previous studies (16,(26)(27)(28). We noticed that thrb ja27 mutant exhibited a moderate but significant increase in sws2 gene expression ( Fig.…”
supporting
confidence: 86%
“…Several trans‐regulatory factors have been identified as critical regulators for the cell type‐specific expression of opsin genes in zebrafish. Thyroid hormone (TH) receptor B ( thrb ) is required for LWS expression (DuVal & Allison, 2018; Suzuki et al, 2013; Volkov et al, 2020), and the transcription factor Tbx2b is essential for SWS1 expression (Alvarez‐Delfin et al, 2009). Also, it was shown that six6 and six7 regulate the expression of SWS2 and RH2 genes (Ogawa et al, 2019; 2015).…”
Section: Trans‐regulation For Rh2 and Lws Expression In Zebrafishmentioning
confidence: 99%
“…It is also possible that other transcription factors induced by RA and TH affect LWS expression. A recent transcriptomic analysis in zebrafish retinas upon the knockout of thrb found only five genes are down‐regulated, among which three (LWS‐1, LWS‐2, and miR‐726, a conserved microRNA gene located between SWS2 and LAR) are from the LWS locus (Volkov et al, 2020). These results may indicate that the TH receptor directly regulates LWS expression.…”
Section: Control Of Lws Expression By Ra and Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, thyroid hormone (TH) is a key regulator of postembryonic development (Laudet, 2011; McMenamin and Parichy, 2013; Tata, 1998). TH is necessary and sufficient for all aspects of amphibian metamorphosis (Tata, 1998) and has been shown to regulate development of the adult pigment pattern, pancreas, skeleton and nervous system in the zebrafish (Hu et al, 2020; Hu et al, 2019; Hur et al, 2017; Matsuda et al, 2017; McMenamin et al, 2014; Saunders et al, 2019; Volkov et al, 2020). One of the many important TH target organs in human is the skin.…”
Section: Introductionmentioning
confidence: 99%